Development of Table Tennis Learning Media Based on Android Applications - Melya Nur Herliana; Haikal Millah; Selly Purnama (Universitas PGRI Palembang, 2022)
This study aims to develop a table tennis learning media based on an android application that is tested for its product feasibility and can be used in lectures both online and as a guide in offline lectures. The research carried out was only up to the development or development stage because the other purpose of this research was only to develop and produce a table tennis learning media product based on an android application called